Key performance indicators for destination management in developed economies: A four pillar approach - John C. Crotts; Vincent P. Magnini; Esra Calvert (Annals of Tourism Research Empirical Insights, 2022)
This conceptual paper puts forth sources of secondary and primary data that can assist destinations in developed countries track and ultimately improve their communities' tourism performance and resilience across four pillars of tourism sustainability: visitor economy, resident support, workforce satisfaction, and environmental health. Such data sources can be used by community leaders to formulate key performance indicators (KPIs) critical in building resilience. The impetus behind these proposed solutions is based on the assumption that the high cost and complexity of collecting and analyzing data on an ongoing basis have plagued the broad adoption of communities engaging in sustainable initiatives. We contend that given access to suitable data, destinations can be better managed as ecosystems in line with sustainable community objectives.
Keywords: 330; Tourism sustainability; Resilience; Continuous improvement process